The Effect of Platelet Activity, ABCB1 Genetic Polymorphism, and Renal Function on the Development of Ticagrelor-Related Dyspnea in Patients with Acute Coronary Syndrome - Tamakauskas V; Žaliūnas R; Lesauskaitė V; Kupstytė-Krištaponė N; Čiapienė I; Šakalytė G; Plisienė J; Skipskis V; Tatarūnas V (Dove Medical Press, 2024)
Vytenis Tamakauskas,1,2 Remigijus Žaliūnas,2 Vaiva Lesauskaitė,1 Nora Kupstytė-Krištaponė,1,2 Ieva Čiapienė,1 Gintarė Šakalytė,1,2 Jurgita Plisienė,2 Vilius Skipskis,1 Vacis Tatarūnas1 1Institute of Cardiology, Medical Academy, Lithuania University of Health Sciences, Kaunas, LT-50009, Lithuania; 2Department of Cardiology, Faculty of Medicine, Medical Academy, Lithuania University of Health Sciences, Kaunas, LT-50009, LithuaniaCorrespondence: Vytenis Tamakauskas, Institute of Cardiology, Medical Academy, Lithuania University of Health Sciences, Sukilėlių g. 15, Kaunas, LT-50009, Lithuania, Tel/Fax +370 675 77 393, Email vytenis.tamakauskas@lsmu.ltPurpose: The aim of this study was to determine the effect of ABCB1 genetic polymorphism and renal function on the occurrence of ticagrelor-related dyspnea.Patients and Methods: A total of 299 patients with acute with type 1, 2, or 3 myocardial infarction (with and without ST-segment elevation), who underwent coronary angiography and PTCA with stent implantation and were treated with antiplatelet drugs (ticagrelor and aspirin), were enrolled in this prospective study. For all enrolled patient's platelet aggregation (induction with high-sensitivity adenosine diphosphate, ADP HS) testing was performed using a MULTIPLATE® analyzer. Venous blood was also collected for genotyping.Results: Patients experiencing ticagrelor-related dyspnea had lower ADP HS value (ADP HS ≤ 19.5 U; OR = 2.254; P = 0.009), higher creatinine concentration (> 90 μmol/l; OR = 3.414; P = 0.019), and lower GFR value (< 60 mL/min/1.73 m2; OR = 2.211; P = 0.035). ABCB1 T allele was associated with ticagrelor-related dyspnea (OR = 2.550; P = 0.04).Conclusion: Ticagrelor-related dyspnea was found to be related to low platelet aggregation, increased plasma creatinine concentration, decreased GFR, and ABCB1 T allele. Carriers of the ABCB1 T allele had a higher plasma creatinine concentration that could be associated with an inhibitory effect of ticagrelor on P-glycoprotein function.Keywords: ticagrelor, ticagrelor pharmacogenomics, ticagrelor related dyspnea, ABCB1 gene polymorphisms, platelet aggregation